PERSEPSI PELAJAR TERHADAP KONTEN PORNOGRAFI DI KECAMATAN PAMIJAHAN PADA MEDIA SOSIAL - Prakoso, Adrie Bagus; Yusnita, Titien; Muslikhah , Febri Palupi (JURNAL SAHID DA'WATII, 2023)
Pornography causes distorted perceptions of social reality or excessive perceptions of various levels of sexual behavior in the general population. Some cases indicate that individuals who repeatedly view pornography may develop mental problems/disorders regarding sexuality. Sexually provocative children may be at increased risk of becoming sexual victims. Furthermore, engaging in sexual social interactions and viewing it as a game can cause emotional disturbances to other children who are exposed at inappropriate ages and sometimes even trigger sexually aggressive behavior. This research aims to understand the perceptions of students in the Pamijahan District regarding Pornography Content on Social Media. The informants in this study are high school students in the Pamijahan district, and the research uses a qualitative method with purposive sampling technique. Adolescents' perceptions of pornography content on social media are processes that allow individuals to choose, categorize, and interpret specific stimuli from the environment and processes that influence individuals.